How digital payments can benefit entrepreneurs - Leora Klapper (IZA World of Labor, 2017)
Digital payment systems can conveniently and affordably connect entrepreneurs with banks, employees, suppliers, and new markets for their goods and services. These systems can accelerate business registration and payments for business licenses and permits by reducing travel time and expenses. Digital financial services can also improve access to savings accounts and loans. Electronic wage payments to workers can increase security and reduce the time and cost of paying employees. Yet, there are challenges as many entrepreneurs and employees lack bank accounts, digital devices, and reliable technology infrastructure.
Keywords: 330; entrepreneurship; wages; financial inclusion; digital payments